PERANAN TEKNOLOGI NUKLIR DI BIDANG ARKEOLOGI INDONESIA DAN PENGEMBANGANNYA - Wisjachudin, Faisal; F. Lahagu; Widodo, Djoko; Basuki, Kris Tri; A. Taftazani; Widayati, Suci (Berkala Arkeologi, 2000)
The results of the analysis show that the role of nuclear engineering for archaeological evidence is very useful and needs to be developed and carried out by experts in general, especially in the field of archaeology. As it is known that the analysis using the ordinary chemical analysis method has several weaknesses, including not being able to analyze certain elements, requiring quite a lot of samples because the analysis for one element requires one sample. Meanwhile, the analysis using the relative dating that has been done by archaeologists will be more accurate if it is followed by absolute dating.